Short Communication: Correlation, path analysis, and heritability of phenotypic characters of bread wheat F2 populations - YUDIWANTI WAHYU; NURWANITA EKASARI PUTRI; TRI KOESOEMA NINGTYAS; SURJONO HADI SUTJAHJO; AMIN NURa (Society for Indonesian Biodiversity, 2018)
Wahyu Y, Putri NE, Trikoesoemaningtyas, Sutjahjo SH, Nur A. 2018. Short Communication: Correlation, path analysis, and heritability of phenotypic characters of bread wheat F2 populations. Biodiversitas 19: 2344-2352. Wheat varieties are still limited for Indonesia. A high yield wheat plant is necessary to be assembled by selecting plants from a segregated population. The selection will need information on some characters that contribute to the high yield and the relationship among the observed characters. This study aimed to determine the relationship between characters and the effects of the observed characters to grain yield per plant. This research was conducted from July 2017 to March 2018 at Balithi Experimental Farm (1100 m asl.), Cipanas, Cianjur District, West Java, Indonesia. The genetic material used were three F2 population of bread wheat (G1/Se, HP/Se, and Ja/Se) and four parent genotypes. Observations were made on each individual of F2 populations. Parent genotypes were planted by using completely randomized block design with three replications. The results showed that the number of a grain of non-main spike and the number of grain per plant characters had a high correlation in each F2 population and these characters also had positive and significant direct effect to grain weight per plant. It could be a character selection for high yield breeding program. The broad sense heritability was medium to a high value for all characters in F2 G1/Se and HP/Se populations.